Business Opportunities for Patchouli Oil Derivative Pomade Products - Putra, Denni Yansyah; Rizky, T. M. Hilal; Sari, Devita; Delvi, Restina; Nurtika, Annisa Dwi; Ernawati, Ernawati (Journal of Patchouli and Essential Oil Products, 2023)
Derivative pomade products from patchouli oil are one of the products formulated with patchouli oil, which adds economic value and can be used as a business to increase income. This study aims to analyze the market share and financial analysis of the innovative pomade derivative product business using patchouli oil in Banda Aceh City. This study used primary and secondary data. The data were analyzed using descriptive quantitative methods. From the financial analysis, this business obtained a monthly profit of Rp. 1,508,843.65 with an R/C ratio 1, BEP unit total production, and BEP sales the selling price of the pomade product. This means that the business is viable. In addition, the payback period is achieved within 2.4 months after the business is implemented. The market share analysis results show that this product can capture a market share of 18.7% in Banda Aceh City.Keywords: business feasibility, market share, pomade